Airport Planning & Management, Seventh Edition - Young, Seth B.; Wells, Alexander T. (McGraw-Hill Education, 2019)
The definitive guide to airport planning and management?fully updated with the latest advances in the industry. This thoroughly revised guide covers all aspects of airport infrastructure?from the airfield and runway to airspace, air traffic control, and terminal and security systems. Airport Planning & Management, Seventh Edition clearly explains the FAA?s National Plan of Integrated Airport Systems (NPIAS), historical and current legislation and regulations, FAR Part 139, and more. You?ll explore cutting-edge concepts such as automation, smart baggage handling, enhanced security, and analytics. Updated questions for review and discussion will bring new insights to your knowledge of how airports are planned and managed. Coverage includes: ?An introduction to airports and airport systems ?Airport and airport systems organization and administration ?Historical and legislative perspectives ?The airfield ?Airspace and air traffic management ?Airport operations management under FAR Part 139 ?Airport terminals and ground access ?Airport security ?Airport financial management ?Economic, political, and social role of airports ?Airport planning ?Airport capacity and delay ?The future of airport management.